Australian trees and shrubs: species for land rehabilitation and farm planting - Doran, J.C.; Turnbull, J.W. (Australian Centre for International Agricultural Research, 1997)
This book is an extensive revision and enlargement of a 1986 publication ‘Multipurpose Australian trees and shrubs: lesser-known species for fuelwood and agroforestry’. It is intended as a reference text for all those concerned with selecting and growing trees and shrubs in rural areas of developing countries and in the more tropical parts of Australia. Descriptions of the botanical, ecological, silvicultural and utilisation characteristics of potential species are provided. With continued decline in the area of tropical forests and woodland, and degradation of remaining forests, alternative sources are needed for the products and services of these forests. Development of small-scale plantations to provide wood and other tree products is increasing. Smallholders, especially in Asia, are taking the option of growing trees on their land as woodlots, line plantings or with crops in a variety of agroforestry systems. The search for suitable trees is focussing on improving productivity of those species already in use and finding new species to meet particular environmental and social situations. Australia has rich genetic resources of woody plants, many of which are adapted to harsh climatic conditions and nutrient deficient soils. Evaluation of Australian trees to meet the needs of resource-poor people in developing countries concentrated on species with a tropical and subtropical distribution. Desirable characteristics include ability to provide products and services in addition to fuelwood, adaptability, easy maintenance and establishment, and tolerance of extreme environments.